Large-Scale Direct Shear Test on Tire Slice Reinforced Crushed Concrete Particles - Qiang Ma; Hang Shu; Jia Mou; Lihua Li; Zhenyi Zheng (Advances in Materials Science and Engineering)
In order to study the mechanical properties of tire slices reinforced crushed concrete particles, a series of shear tests were carried out under the conditions of different vertical loads, different tire volume contents, and different shear rates. The test results show that the addition of tire slices can increase the internal friction angle and cohesion of concrete particles, therefore increase the shear strength of crushed concrete particles. The peak shear stress increases with the increase of vertical load. However, with the increase of the tire volume content, the reinforcement effect of the tire slices first increases and then decreases, and the effect is best when the tire volume content is 4%. Under the vertical load of 60 kPa, the reinforcement effect of 4% tire volume content is the best, and the peak shear stress increases by 46.53%. Additionally, the shear rate has a little effect on the peak shear stress. The larger the shear rate is, the smaller the shear displacement is and the faster the shear strength decreases. The smaller the shear rate is, the more gently the shear strength decreases.